Respon Pertumbuhan dan Hasil Tanaman Bawang Merah Varietas Bima (Allium Ascalonicum.L) Terhadap Berbagai Kemiringan Talang Pada Sistem Hidroponik NFT - Intan Intan Permatasari; Bastaman Syah; Yayu Sri Rahayu (Peneliti.net, 2021)
The purpose of this research is to get the right slope of the gutters for growth and yield of Shallot (Allium ascalonicum L.) varieties of Bima. The experiment was conducted in the village of Nagrak , East Darangdan District, Purwakarta District, West Java Province. from June to August 2021. The research used experiment method with design of Randomized Group of a single factor, consisting of 7 treatments and 4 replication namely A (1%), B (3%), C (5%), D(7%), E (9%), F(11%), G (13%). The parameters measured in this study were plant height, number of leaves, number of tillers, number of tubers, tuber diameter, wet tuber weight per plant, wet tuber weight per installation, dry tuber weight per plant, dry tuber weight per gutter. The results showed that the administration various type of gutter slope affected plant height, number of leaves, number of tillers, number of tubers, tuber diameter, wet tuber weight per plant, wet tuber weight per gutter, dry tuber weight per plant, dry tuber weight per gutter. Shallot (Allium cepa ascalonicum L.) Bima variety. Treatment E (9%) gave the highest yield on tuber weight per gutter (159,92 g), with the number of tubers per plant (7,92 tuber).